The Norm of Rate Fixing of Islamic Banks Based on Conventional Bank Rates: Evidence from Indonesia - Fakhrina, Agus; Islahuddin (Jurnal Hukum Islam, 2023)
Interest rate fixing is a monetary tool used to control the money supply and hence inflation by the central bank. However, it cannot be applied to Islamic banks due to the prohibition of interest in Islam. This paper examines whether the central bank may implement rate fixing for Islamic banks, given that interest is forbidden, and the fixing of prices by the government is also generally prohibited, according to Hadith and the consensus of Islamic jurists. A documentation study was conducted to comprehend the viewpoints of classical and contemporary Islamic jurists and the National Shariah Board−Indonesian Ulama Council's fatwa. The analysis used Islamic law methodology (uşūl fiqh), which included combining the opinions of classical and contemporary Islamic jurists through the al-jam’u and the legal maxim approach, "al-‘ādah muhakkamah" approach to the custom practiced by Islamic banks, and the maqāşid approach. The research findings illustrate that Islamic banks have been using rates to calculate profits as the National Shariah Board−Indonesian Ulama Council accepts the notion of the time value of money, provided it is not utilized in loan transactions. This condition could enable the central bank to set the rates for Islamic banks, which is an effective tool for controlling the money supply and achieving economic stability, thus contributing to the realization of community welfare (maslahah 'ammah).